Multiferroic CoFe2O4–BiFeO3 core–shell nanofibers and their nanoscale magnetoelectric coupling. Issue 5 (4th March 2014) - Zhu, Qingfeng; Xie, Ying; Zhang, Jing; Liu, Yuanming; Zhan, Qingfeng; Miao, Hongchen; Xie, Shuhong
Abstract